Landscape configuration in seagrass meadows and its influence on carbon stock in reef lagoon systems - Herrera-Silveira, Jorge Alfredo; Palafox-Juárez, Erika Betzabeth; Mendoza-Martínez, Juan Enrique; Montero Muñoz, Jorge Luis; Teutli Hernández, Claudia (Frontiers in Marine Science, 2025)
Seagrass meadows are one of the most important and productive habitats in coastal zones worldwide and are considered one of the most significant coastal ecosystems in terms of contributing to carbon storage on a global scale, mitigation, and adaptation to climate change. Seagrass functional processes depend on their connectivity and interactions with neighboring habitats and variables closely tied to their spatial configuration, which can only be understood through large-scale analysis. This study evaluated the influence of seagrass meadow configuration on the carbon storage of ten reef lagoons in Veracruz Reef Systems National Park. A total of 513 sampling sites were identified using unsupervised classification of WorldView2 images. Seagrass cover and substrate data were collected at each site to identify specific landscape types, and the top 25 cm of soil organic carbon (SOC) and biomass (BOC) samples were collected at 153 sites to estimate the carbon stock and its relationship with landscape configuration. Three landscape types were identified across the lagoons: low-density seagrass over rocks, medium-density seagrass over sand and rock, and high-density seagrass over sand. The range of carbon stock was 0.7 ± 0.1 Mg C ha-1 to 5.9 ± 1.2 Mg C ha-1 in biomass and 19.1 ± 4.5 Mg C ha-1 to 117.5 ± 5.3 Mg C ha-1 to 0.25 m deep soils. Landscape ecology metrics were explored to evaluate the relationship between the landscape configuration and variation in soil carbon (SOC5cm) stock, including 5 cm deep soil. The results revealed a relationship between mean patch size (r2 = 0.3511, p = 0.0761), aggregation index (r2 = 0.5036, p = 0.0177), and percentage of like adjacencies (r2 = 0.4099, p = 0.0429) with SOC5cm variations in the southern landscape and relationship with edge density in the northern landscape (r2 = 0.456, p = 0.08). This study suggests that seagrass landscape configuration influences carbon stocks, and therefore, emerging factors, both natural and anthropogenic, typical of the VRSNP, could contribute to the unexplained variability in landscape configuration. This study provides evidence of landscape characteristics's importance and continuity characteristics in seagrass soil carbon stocks.